Advising environmental defense - Rosenthal, Jean W. (SAGE Knowledge. Cases., 2017)
Fred Krupp, the President of Environmental Defense, received the first call from the Texas Pacific Group (TPG) requesting that EDF, along with NRDC, participate in the negotiations surrounding the possible buy-out of TXU. Krupp referred the call to James D. Marston, Regional Director of Environmental Defense's Texas Office and head of the Texas Climate Initiative, who had been in the trenches fighting TXU's plans to build coal-fired electric generation plants in Texas. Neither Krupp nor Marston knew why these two environmental groups had been brought in at the 11th hour to possibly bless this private equity deal, though Marston had a number of hunches.